Early literacy assessment among kindergarten teachers in Indonesia: a phenomenological study - Christianti, Martha; Retnowati, Trie Hartiti; Wening, Sri; Hasan, Aminuddin; Ratnawati, Heri (Eurasian Society of Educational Research, 2022)
The study aims to identify how kindergarten teachers perform early literacy assessments in the classroom and the challenges these teachers have in performing such assessments. During the study, the data were gathered through an in-depth interview in the form of a forum group discussion (FGD). Then, the phenomenological data were attained from 30 public and private Kindergarten teachers. The researchers could illustrate how these kindergarten teachers assessed their children's early literacy through these data. Furthermore, the study results show that the teachers' literacy knowledge has been sufficient and that the literacy programs for the children have been variously designed in each school. The teachers' techniques in performing the early literacy assessment are observation and documentation (portfolio), and the measurement of literacy skills itself refers to the scope of literacy. Concerning the findings, numerous obstacles and expectations that kindergarten teachers have are also discussed within the study.